How do you solve 6= \sqrt { - 5- 3u } + 2?

2 Answers
May 29, 2017

u = - 7

Explanation:

subtract (-2) from both sides, we get

6-2=sqrt(-5-3u) +2-2

rArr 4= sqrt(-5-3u) [ Note: squaring both sides]

rArr 4^2=[sqrt(-5-3u)]^2

rArr 16 = -5-3u

rArr 3u=-5-16 or -21

rArr u -21/3 or -7

May 29, 2017

u = -7

Explanation:

6 = sqrt(-5 - 3 u) + 2

We can use some simple algebra to work this out.

6 = sqrt(-5 - 3 u) + 2

6 -2= sqrt(-5 - 3 u)

4= sqrt(-5 - 3 u)

4^2 = -5 - 3 u

16 = -5 - 3 u

16 = -5 - 3 u

16 + 5= - 3 u

21= - 3 u

u = 21 ÷ -3

color(blue)(u = -7

We can now substitute u for -7 to prove that we are correct.

6 = sqrt(-5 - 3 u) + 2

6 = sqrt(-5 - 3 xx 7) + 2

6 = sqrt16 + 2

6 = 4 + 2

6 = 6